the analysis of patent results of scientific research in federal universities of Russia in 2011-2019. - Shegelman I. R., Vasilyev A. S. (Relevant lines of scientific research: theory and practice, 2019)
the analysis of patent results of scientific research in federal universities of Russia in 2011-2019.
Keywords: интеллектуальная собственность; объекты интеллектуальной собственности; патент; результаты интеллектуальной деятельности; intellectual property; knowledge base; patent; федеральный университет; базы знаний; federal university